2023
DOI: 10.1007/s00401-023-02612-x
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve inflammation contributes to dysautonomia in COVID-19

Marcel S. Woo,
Mohsin Shafiq,
Antonia Fitzek
et al.

Abstract: Dysautonomia has substantially impacted acute COVID-19 severity as well as symptom burden after recovery from COVID-19 (long COVID), yet the underlying causes remain unknown. Here, we hypothesized that vagus nerves are affected in COVID-19 which might contribute to autonomic dysfunction. We performed a histopathological characterization of postmortem vagus nerves from COVID-19 patients and controls, and detected SARS-CoV-2 RNA together with inflammatory cell infiltration composed primarily of monocytes. Furthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This may be attributed to the fact that our subjects consisted of young college students, and none of them were hospitalized due to COVID-19 infection. A recent study had indicated that SARS-CoV-2 induced vagal neuropathy, leading to autonomic dysfunction and potential long-term impairment of autonomic function (44) . Additionally, a study found that SARS-CoV-2 infection increased sympathetic nerve activation in young individuals, but had no signi cant effect on resting hemodynamics and speculated that the impact of COVID-19 on endothelial function and arterial stiffness may be more pronounced in older individuals (45) .…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the fact that our subjects consisted of young college students, and none of them were hospitalized due to COVID-19 infection. A recent study had indicated that SARS-CoV-2 induced vagal neuropathy, leading to autonomic dysfunction and potential long-term impairment of autonomic function (44) . Additionally, a study found that SARS-CoV-2 infection increased sympathetic nerve activation in young individuals, but had no signi cant effect on resting hemodynamics and speculated that the impact of COVID-19 on endothelial function and arterial stiffness may be more pronounced in older individuals (45) .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, fatigue and airway disorders in long COVID patients are other symptoms that have been associated with dysautonomia [ 12 ]. In particular, the latest studies suggest that SARS-CoV-2 may induce vagus nerve inflammation followed by autonomic dysfunction, which might contribute to critical disease courses and dysautonomia observed in long COVID [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the acupoint selection in this case report, previous studies have indicated that acupuncture at sympathetic (AH6a), shenmen (TF4), and point zero could regulate sympathetic nerve functions and induce parasympathetic activation to improve insomnia ( 10 ). Moreover, given that vagal dysregulation is an important contributor to post-COVID sequelae ( 11 ), needling at point zero, which is located along the distribution paths of the auricular branch of the vagus nerve (ABVN), can neuromodulate the vagus nerve to treat psychiatric symptoms in this patient. In addition, a previous research study has revealed that needling at point zero can create a sense of calmness and homeostasis, thereby relieving anxiety ( 12 ).…”
Section: Discussionmentioning
confidence: 99%